Making vulnerable groups able to connect socially and digitally—opportunities and pitfalls - Faye, Reidun; Ravneberg, Bodil Elise (Frontiers in Education, 2024)
Introduction: This article addresses digital and social inclusion of adults with potential low digital skills. The article presents a case study of how digital learning activities (DLAs) as a service to refugees, immigrants, senior citizens, and young adults neither in education, employment, or training (NEETs), are delivered outside the formal educational system by two libraries and one civic organization in Norway, Denmark, and Belgium. Through the theoretical lenses of social capital building, co-creation and co-producing, the article analyzes how the DLA’s were organized and tailored for the participant’s needs, with an emphasis on cooperation efforts with local sub-partners and representatives from the target groups. Methods: A multiple case-design was applied using a process tracing method combining qualitative and quantitative techniques. To measure the partner organizations’ experiences from the project, we conducted participant observation, personal and focus group interviews, in addition to self-reporting schemas about how they organized the DLA’s. Surveys were conducted to measure the participants’ experiences. Results: By combining literature and theoretical approaches from several fields; digital inclusion, public and civil organization research – with a particular focus on libraries, and their role in educating refugees and other vulnerable groups, the article provides new insights on how public and non-public organizations in local communities can work together to tailor-make DLAs and contribute to the promotion of digital inclusion. Discussion: Libraries and civic organizations have potential to reach out to vulnerable people in local communities, to provide innovative DLA’s and to connect both people and organizations. Vital for recruitment of participants and to find the right level of digital/technical ambition is to closely co-create and co-produce with representatives from other local organizations in both civil and public sector during the whole process. Co-creating activities with actors representing the target group in the planning phase as well as co-producing them in the implementation phase, are important prerequisites. The article discusses the challenges of trust-building, of finding the right level of digital ambition as well as developing long-term digital activities as important factors for the promotion of digital inclusion.